Osteogenesis imperfecta type II with patent ductus arteriosus, severe persistent pulmonary hypertension, sepsis and severe thrombocytopenia in a neonate: A case report - Mansoor Aslamzai; Mohammad Sharif Sediqi; Mohmand Mangal; Ataullah Shinwarie (Elsevier, 2024)
Background: Osteogenesis imperfecta type II is a rare congenital anomaly that usually causes death in utero or shortly after birth. Case Presentation: This study reports a rare case of osteogenesis imperfecta type II in an Afghan girl who was one day old. The defect was accompanied by a patent ductus arteriosus, severe persistent pulmonary hypertension of the newborn, sepsis, severe thrombocytopenia, and low birth weight during the first four days of life. These disorders were diagnosed by medical history, physical examination, blood investigation, computed tomography, x-ray, and doppler ultrasonography. On the fifth day of life, the newborn suffered an abrupt cardio-pulmonary arrest that resulted in her death, presumably due to brainstem compression or severe persistent pulmonary hypertension of the newborn. Conclusion: Osteogenesis imperfecta type II can result in life-threatening complications during the first week of life.